2007
DOI: 10.1103/physrevlett.99.043002
|View full text |Cite
|
Sign up to set email alerts
|

Rectified Momentum Transport for a Kicked Bose-Einstein Condensate

Abstract: We report the experimental observation of rectified momentum transport for a Bose-Einstein Condensate kicked at the Talbot time (quantum resonance) by an optical standing wave. Atoms are initially prepared in a superposition of the 0 and −2 k l momentum states using an optical π/2 pulse. By changing the relative phase of the superposed states, a momentum current in either direction along the standing wave may be produced. We offer an interpretation based on matter wave interference, showing that the observed e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
132
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(134 citation statements)
references
References 25 publications
2
132
0
Order By: Relevance
“…For a ␦-kicked rotor model with time symmetry broken by a two-period kicking cycle ͑asymmetric temporal drive͒, directed growth of momentum has been detected by Jones et al ͑2007͒. For a phase-dependent initial preparation of a Bose-Einstein condensate kicked at resonance, a momentum acceleration has been observed by Sadgrove et al ͑2007͒ at zero quasimomentum, while for an arbitrary quasimomentum directed quantum Brownian transport has been realized by Dana et al ͑2008͒. The last experiment also showed that the intrinsic experimentally nonavoidable finite width in quasimomentum causes a suppression of the acceleration, eventually leading to a saturation effect after short times.…”
Section: Hamiltonian Quantum Ratchet For Cold Atomsmentioning
confidence: 96%
“…For a ␦-kicked rotor model with time symmetry broken by a two-period kicking cycle ͑asymmetric temporal drive͒, directed growth of momentum has been detected by Jones et al ͑2007͒. For a phase-dependent initial preparation of a Bose-Einstein condensate kicked at resonance, a momentum acceleration has been observed by Sadgrove et al ͑2007͒ at zero quasimomentum, while for an arbitrary quasimomentum directed quantum Brownian transport has been realized by Dana et al ͑2008͒. The last experiment also showed that the intrinsic experimentally nonavoidable finite width in quasimomentum causes a suppression of the acceleration, eventually leading to a saturation effect after short times.…”
Section: Hamiltonian Quantum Ratchet For Cold Atomsmentioning
confidence: 96%
“…The reversed peak is very sensitive to variations of and other parameters breaking time reversal symmetry, and therefore this setup can be used as a sensitive Loschmidt interferometer to explore such a symmetry breaking (e.g., a gravitational field component along the optical lattice gives a shift in which affects the Loschmidt peak). The parameters considered here are well accessible to nowadays experimental setups (see, e.g., [13][14][15][16][17][18][19][20] ). The realization of our proposal will shed a new light on the long-standing Boltzmann-Loschmidt dispute on time reversibility.…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%
“…This model has been built up experimentally with cold atoms in kicked optical lattices [13][14][15][16]. Recent progress allowed to implement this model with ultracold atoms and Bose-Einstein condensates (BEC) [17][18][19][20], with high-precision subrecoil definition of the momentum of the atoms, allowing, for example, to observe [17,19] high order quantum resonances [21]. We show that these experimental techniques allow to perform time reversal for a significant part of the atoms.…”
mentioning
confidence: 99%
“…Cold atoms in optical lattices are one of the main examples of successful implementations and theoretical developments [11,12]. Also, Bose-Einstein condensates have been transported (for particular initial conditions) by using purely quantum ratchet accelerators [13]. In this case, the current has no classical counterpart [14], and the energy grows ballistically [15,16].…”
Section: Introductionmentioning
confidence: 99%